Analisis Kerja Petugas Flight Coordinator dalam Mencapai On-Time Performance di Bandar Udara Internasional Soekarno-Hatta Tangerang Banten: Penelitian pada Maskapai TransNusa di PT. Jasa Angkasa Semesta - Shiva Amalia; Zenita Kurniasari (MES Bogor, 2024)
Flight Coordinators have a very important role in maintaining On-Time Performance (OTP) or punctuality in flight operations. A number of obstacles they experience can affect on-time performance and must be managed well. The aim of this research is to determine the work of flight coordinator officers in achieving on time performance at Soekarno Hatta Tangerang Banten International Airport. This research uses a qualitative method using primary data obtained through interviews and observation, secondary data through literature study and documentation. The data collection techniques used were observation (participating in the field), interviews and documentation. Interviews were conducted with supervisors and heads of narrow bodies, as well as TransNusa flight coordinators. Data analysis techniques by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research are the suitability of the flight coordinator in carrying out work according to his job desk, starting from the plane not yet landing to the pushback plane. Work factors or obstacles that are often faced by flight coordinators are late arrival and parking stands in remote areas. Efforts that can be made to overcome these obstacles are carrying out quick handling and speeding up coordination with related units in order to achieve on-time performance targets.